Factors associated with the incidence of stunting in children aged 6-24 months in the Cileungsi area - Murtiningsih, Murtiningsih; Fitriani, Lia; Putri, Desty Ayu Pratama (International Journal of Multidisciplinary Approach Research and Science, 2023)
Stunting is a chronic malnutrition problem caused by a lack of nutritional intake over a long period of time, resulting in growth disorders, namely short children. This study aims to determine the factors associated with the incidence of stunting in toddlers aged 6-24 months in Cileungsi area. This method of research is a correlational study with a cross sectional approach. Sampling was carried out using non-probability sampling using total sampling. The sample in this study was 50 respondents in the Cileungsi area, namely mothers with toddlers aged 6-24 months who were willing to be respondents. Data was collected using interviews and height observations. The results showed that 56% of children aged 6-24 months experienced stunting (28 children), 3% (6 children) had low birth weight history, 14% (7 mothers) had hemoglobin levels during pregnancy is anemia, 56% did not receive exclusive breastfeeding (28 children). The results of the multivariate analysis showed that exclusive breastfeeding was the variable that had the significant relationship with the incidence of stunting in children aged 6-24 months in the Cileungsi area (p value = 0.000). Recommendations it is hoped that volunteer will always provide motivation, enthusiasm, education, and conduct home visits to the community regarding the importance of exclusive breastfeeding.